Clean And Healthy Living Behavior (PHBS) Education In Preventing ISPA In Soldiers At The 22/Om Brigif Health Police - Prima Dewi K; Irma Aryanti (International Journal of Health Engineering and Technology, 2026)
The 22nd Infantry Brigade (Brigif 22/OM) Health Police reported 87 cases of ISPA among soldiers in 2025 due to high mobility and dense interaction, with suboptimal PHBS as the main factor. This community service activity aims to increase soldiers' knowledge and awareness in implementing PHBS as an effort to prevent ISPA. The participants in this activity were 30 soldiers. The evaluation was conducted using a pre-test and post-test with 10 closed-ended questions to measure changes in knowledge levels. The results showed a significant increase in knowledge from an average score of 62% (pre-test) to 88% (post-test), the good category increased from 26.7% to 80%. PHBS education is effective as a promotive intervention in the military environment, and periodic replication with long-term behavioral measurements is recommended.